2022
DOI: 10.3390/microorganisms10030510
|View full text |Cite
|
Sign up to set email alerts
|

Alum Addition Triggers Hypoxia in an Engineered Pit Lake

Abstract: Here, we examine the geobiological response to a whole-lake alum (aluminum sulfate) treatment (2016) of Base Mine Lake (BML), the first pilot-scale pit lake established in the Alberta oil sands region. The rationale for trialing this management amendment was based on its successful use to reduce internal phosphorus loading to eutrophying lakes. Modest increases in water cap epilimnetic oxygen concentrations, associated with increased Secchi depths and chlorophyll-a concentrations, were co-incident with anoxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…However, several key issues with EPLs need investigation to understand their environmental implications. , The first full-scale demonstration of EPL (∼8 km 2 surface area) was commissioned in 2013 after FFT was transferred from the active Mildred Lake Settling Basin (tailings pond) into the closed West In-Pit mine site to create Base Mine Lake (BML) as a potential FFT reclamation strategy . Since then, several aspects of BML development and progression into environmentally functional aquatic ecosystem have been under investigation, particularly in the cap water zone of BML, at the laboratory and full scale including dissolved oxygen consumption in response to biogeochemical changes; alum addition , and role of biofilms and carbonate mineral dissolution in turbidity reduction; , wind action effects on physical processes (mixing, oxygenation, and turbidity); nitrogen cycling; and the effect of chemical fractions on fish reproduction . The sustainability of these ecological processes in cap water is strongly influenced by cap water chemistry which, in turn, is linked to FFT porewater chemistry via advective and diffusive chemical flux from FFT to cap water; the latter process will dominate as FFT settlement slows with time. ,, While investigating the effect of cap water chemistry on ecological processes, it is important to understand the driving forces so as to predict longevity of chemical flux/partitioning and project EPL evolution to a functional aquatic ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…However, several key issues with EPLs need investigation to understand their environmental implications. , The first full-scale demonstration of EPL (∼8 km 2 surface area) was commissioned in 2013 after FFT was transferred from the active Mildred Lake Settling Basin (tailings pond) into the closed West In-Pit mine site to create Base Mine Lake (BML) as a potential FFT reclamation strategy . Since then, several aspects of BML development and progression into environmentally functional aquatic ecosystem have been under investigation, particularly in the cap water zone of BML, at the laboratory and full scale including dissolved oxygen consumption in response to biogeochemical changes; alum addition , and role of biofilms and carbonate mineral dissolution in turbidity reduction; , wind action effects on physical processes (mixing, oxygenation, and turbidity); nitrogen cycling; and the effect of chemical fractions on fish reproduction . The sustainability of these ecological processes in cap water is strongly influenced by cap water chemistry which, in turn, is linked to FFT porewater chemistry via advective and diffusive chemical flux from FFT to cap water; the latter process will dominate as FFT settlement slows with time. ,, While investigating the effect of cap water chemistry on ecological processes, it is important to understand the driving forces so as to predict longevity of chemical flux/partitioning and project EPL evolution to a functional aquatic ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported extensive sulfate reduction in similarly sulfate-amended FFT deposits, resulting in the generation of aqueous and gaseous hydrogen sulfide (H2S) (Reid & Warren 2016;Warren et al 2016). Additionally, alum was added to the BML water cap in 2016, resulting in the generation of aqueous sulfide species near the FFT-water interface and a shift in microbial communities, including the appearance of sulfate-reducing bacteria (Jessen et al 2022). As such, the implications of PASS treatment on biogeochemical cycling processes, particularly sulfur cycling, in EPLs must be evaluated.…”
Section: Introductionmentioning
confidence: 99%